Hongaars Hulpcomité voor Bedrijfsopleiding - Gaál, Enikő (Acta Neerlandica, 2015)
The Netherlands, like other Western European countries, did its share in accepting the 1956 refugees. However, it is perhaps not generally known that it tried to choose the refugees on basis of its labour market needs. In light of this it preferred to recruit miners or workers suitable for mining from the Austrian refugee camps. The placement and resumption of studies of university students and the secondary students wishing to go on to universities happened quickly and smoothly, owing to the effective organizational work of the Dutch UAF (Universitair Asylfonds). There were not so bright prospects for young workers. Ede Flór, who was helping as an interpreter at the reception of the refugees, quickly noticed that the further education or professional placement of technical and industrial students did not fit into the plans of the higher circles. According to their plans, a good part of the workers would have been employed by the Limburg and Noordoostpolder mines. To avoid this, for the longer-term benefits and better living conditions of the boys, Ede Flór, confronting the political will, set up the The Relief Committee of Hungarian Industrial Apprentices (Hongaars Hulpcomité voor Bedrijfsopleiding). Among his goals were to let the boys give a try in their profession and/or place them to companies where they can learn a vocation. To intercede for these boys at authorities of the host countries to provide them vocational education. The Relief Committee also organized its own bridge, bilingual courses. In addition, it shouldered the interest representation of the workers, the liaisoning with plants employing Hungarians. The Committee considered its own duty to motivate the working youth to study, did not let these often very young teenagers go astray who, in many cases came without their parents to an unknown world. It did not wish to isolate them from the host society but to foster adaptation, success and better progress in the new and chosen homeland - even if it was initially thought to be temporary. Compared to the already existing and the newly formed Hungarian associations in the Netherlands, the Relief Committee served a very different purpose and thus fulfilled a significant role.